Extracellular vesicles affecting embryo development in vitro: a potential culture medium supplement - Xue, Yamei; Zheng, Haixia; Xiong, Yuping; Li, Kun (Frontiers in Pharmacology, 2024)
Abstract: Extracellular vesicles (EVs) are nanometer-sized lipid bilayer vesicles released by cells, playing a crucial role in mediating cellular communication. This review evaluates the effect of EVs on early embryonic development in vitro by systematically searching the literature across three databases, Embase, PubMed, and Scopus, from inception (Embase, 1947; PubMed, 1996; and Scopus, 2004) to June 30, 2024. A total of 28 studies were considered relevant and included in this review. The EVs included in these investigations have been recovered from a range of sources, including oviduct fluid, follicular fluid, uterine fluid, seminal plasma, embryos, oviduct epithelial cells, endometrial epithelial cells, amniotic cells, and endometrial-derived mesenchymal stem cells collected primarily from mice, rabbits, cattle and pigs. This diversity in EV sources highlights the broad interest and potential applications of EVs in embryo culture systems. These studies have demonstrated that supplementation with EVs derived from physiologically normal biofluids and cells to the embryo culture medium system has positive effects on embryonic development. Conversely, EVs derived from cells under pathological conditions have shown a negative impact. This finding underscores the importance of the source and condition of EVs used in culture media. Further, the addition of EVs as a culture medium supplement holds significant therapeutic potential for optimizing in vitro embryo culture systems. In conclusion, this evaluation offers a thorough assessment of the available data on the role of EVs in embryo culture media and highlights the potential and challenges of using EVs in in vitro embryo production.